Screening for Fabry disease and Hereditary ATTR amyloidosis in idiopathic small‐fiber and mixed neuropathy. Issue 3 (4th December 2018) - Samuelsson, Kristin; Radovic, Ana; Press, Rayomand; Auranen, Mari; Ylikallio, Emil; Tyynismaa, Henna; KäRppä, Mikko; Veteläinen, Matilda; Peltola, Niina; Mellgren, Svein Ivar; Mygland, Åse; Tallaksen, Chantal; et al.
ABSTRACT: Introduction : In this study we assessed the value of genetic screening for Fabry disease (FD) and hereditary ATTR amyloidosis in patients with idiopathic small‐fiber neuropathy (SFN) or mixed neuropathy in a clinical setting. Methods : This was a Nordic multicenter study with 9 participating centers. Patients with idiopathic SFN or mixed neuropathy were included. Genetic sequencing of the TTR and GLA genes was performed. Results : There were 172 patients enrolled in the study. Genetic screening was performed in 155 patients. No pathogenic mutations in the TTR gene were found. A single patient had a possible pathogenic variant, R118C, in the GLA gene, but clinical investigation showed no firm signs of FD. Discussion : Screening for hereditary ATTR amyloidosis and FD in patients with idiopathic SFN or mixed neuropathy without any additional disease‐specific symptoms or clinical characteristics in a Nordic population appears to be of little value in a clinical setting. Muscle Nerve 59 :354–357, 2019 Abstract : See editorial on pages 280–282 in this issue .